Throwing the Moral Dice : Ethics and the Problem of Contingency. - Claviez, Thomas (Fordham University Press, 2021)
From deconstruction to feminism to ecological thought, some of today's most influential thinkers consider the challenge that contingent life poses to the broad claims of ethics. In doing so, they reshape the most debated concepts of moral philosophy.
Description based upon print version of record.
Keywords: Contingency (Philosophy); Ethics.; Ethics; Contingence (Philosophie); Morale.; ethics (philosophy); PHILOSOPHY / Ethics & Moral Philosophy